Daya Kreativitas Mahasiswa dalam Mengikuti Lomba Tata Rias Karakter Halloween Tingkat Nasional - Rohmawati, Helmia Cipta; Harwiyati, Enny; Saputri, Nurulisma (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to determine the creativity of students in participating in the National Competition for the Halloween Makeup category. The research subjects were 8 students from 2 private universities, namely 3 students from the Yogyakarta "AKK" Social Welfare Academy and 5 from the Semarang Mother Kartini Welfare Academy The object of this research is students' creativity in implementing the Character Fantasy Makeup course in competitions. The research method uses a qualitative research method with a descriptive interpretative approach because in this research the author presents the creativity of students who take the character fantasy make-up course. The results of this research show an increase in students' creativity which is actualized through the Halloween make-up competition on October 23 2023 which was held by Makeover at Jogya City Mall Yogyakarta by winning the Hope I championship for students of the Yogyakarta "AKK" Social Welfare Academy and Hope II for students of the Ibu Kartini Semarang Social Welfare Academy. Based on this research, it is hoped that more students will be involved in taking part in similar competitions to hone their creative abilities.